Elusive Balances: Explaining US Commitment to Southeast Asia - Parameswaran, Prashanth. (Tufts University. Tisch Library., 2019)
While the United States has long recognized the general importance of Southeast Asia as a region, the specific level and distribution of U.S. commitment there has been inconsistent and imbalanced, with periods of heightened U.S. involvement followed by years of retrenchment, and certain periods witnessing major imbalances. Yet, to date, there has been little thorough examination of this issue. This dissertation seeks to answer the question of what accounts for the changes in the level and distribution of the United States' commitment to Southeast Asia over time. Using an original theory of foreign policy, it argues that commitment variation is not only the product of power shifts, but the interaction of this with other variables as well including perceptions of threats and the ability of policymakers to mobilize resources for specific ends.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Robert Pfaltzgraff, Jr.; Committee: Jeffrey Taliaferro, and Robert Sutter.; Keywords: Political science, Asian studies, and International relations.